An Outlook of Ḥiyal (Legal Stratagems) and Its Compilations in Islamic Economic Literature - Rafique, Muhammad Omer; Che Abdullah, Ahmad Sufian; Mohd Balwi, Mohd Abd Wahab Fatoni (Online Journal of Research in Islamic Studies, 2021)
Ḥiyal (legal stratagems) means to find an unconventional way to meet an end in a complicated Shari’ah issue. These stratagems should comply with the Maqasid-e-Shari’ah to remain legal. It has a wide application in today’s versatile cutting-edge Shari’ah matters. The research objective of this study is to explore and analyze the manuscripts and compilations from jurists, for and against the application of Ḥiyal (legal stratagems) in Islamic law in the problem-solving procedure. The study finds that Muslim jurists have strived to develop the Ḥiyal theory as a solution to fulfill the needs of the era. Ḥanafi jurists are considered as originators of this concept in Islamic law literature. They have several published compilations containing cases where legal stratagems were applied to solve the problem or may be applied. They were criticized by other jurists for advising such relaxed Ḥiyal, especially by Ḥanbali scholars. The majority of the scholars are of the view that all Ḥiyal are not permissible nor impermissible instead it should be checked on a case-to-case basis. The study is limited to the twelve compilations available to the author. The study uses the content analysis method to achieve its objective. The contemporary Shari’ah scholars may explore these compilations which can support them in finding solutions in the fields of modern Islamic economics and Halal industry.